1975
DOI: 10.1152/ajplegacy.1975.229.2.474
|View full text |Cite
|
Sign up to set email alerts
|

High-output heart failure in the dog: systemic and intrarenal role of angiotensin II

Abstract: Dogs with experimental high-output heart failure (HOF) exhibit marked retention of salt and water secondary to hypersecretion of both renin and aldosterone. The present study was undertaken to evaluate the systemic and intrarenal arteriolar action of angiotensin II (AII) in dogs with HOF and to provide additional information about the role of AII in low-output states. The intravenous infusion of a specific AII antagonist, [Sar1, Ala8]AII (6 mug/kg min-1), into conscious dogs with HOF decreased the mean arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The most likely explanation for the blunted reflex is an interference with the central action of All, since an infusion of All into the vertebral artery leads to tachycardia even in the presence of peripheral All blockade. * 8 Since All facilitates the release of norepinephrine from sympathetic nerve endings, 40 an interruption of this effect could also be responsible for the blunted reflex response to the fall in pressure. There is further evidence of a facilitative action of All on the sympathetic nervous system contributing to the maintenance of blood pressure.…”
Section: !"mentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely explanation for the blunted reflex is an interference with the central action of All, since an infusion of All into the vertebral artery leads to tachycardia even in the presence of peripheral All blockade. * 8 Since All facilitates the release of norepinephrine from sympathetic nerve endings, 40 an interruption of this effect could also be responsible for the blunted reflex response to the fall in pressure. There is further evidence of a facilitative action of All on the sympathetic nervous system contributing to the maintenance of blood pressure.…”
Section: !"mentioning
confidence: 99%
“…19 " 21 Since the angiotensin antagonists themselves possess properties other than those due to antagonism of the polypeptide, studies have been undertaken in which the response to two different types of antagonists, a converting enzyme inhibitor (CEI) and the competitive antagonist Sar'-Ala 8 angiotensin II (SAR), was measured as renin levels were varied over a wide range in dogs by sodium depletion.…”
mentioning
confidence: 99%
“…Acute, partial thoracic inferior vena caval occlusion was induced in an additional 16 dogs. P113 induced progressive, doserelated hypotension and a limited increase in renal blood flow in this model.…”
mentioning
confidence: 99%
“…18 The important conceptual role played by ablation in defining the action of a hormone in an effector system was pointed out by Haber. 4 In the special case of the interaction of the renin-angiotensin system and the kidney, the kidney is both the source of the hormone and the responding organ.…”
Section: Ultiple Observations Over the Years Havementioning
confidence: 99%
“…suggested that angiotensin, in addition to its systemic effect on blood pressure (BP) and on sodium homeostasis through control of aldosterone secretion, may have a direct action on the renal blood supply. 18 The important conceptual role played by ablation in defining the action of a hormone in an effector system was pointed out by Haber. 4 In the special case of the interaction of the renin-angiotensin system and the kidney, the kidney is both the source of the hormone and the responding organ.…”
mentioning
confidence: 99%